PERSPEKSTIF PROFESI GURU DALAM PENDIDIKAN INKLUSI ANAK BERBAKAT USIA DINI - Parwoto; Faizal; Usman (Universitas Negeri Makassar, 2023)
This article examines the teacher professional development model towards the paradigm of inclusive education for early childhood gifted children. The purpose of this paper is to provide an overview of the results of teacher professional development research carried out by the PPG Study Programme at each University Education Personnel Institute. Research subjects: kindergarten teachers; special school teachers; and lecturers. Data collection techniques were carried out with reference studies; questionnaires and interviews. Data were analysed with qualitative descriptive analysis. The results showed that 1) the inclusive education model for gifted children is feasible to be developed in Indonesia by preparing professional teachers in the field through special training. 2) Different approaches and curricula for gifted children in inclusive education settings; 3) A team of professionals and teachers as well as parents working collaboratively in solving problems of gifted children's existence and educational facilities; 4) The development of reciprocal reasonable attitudes in peers in social-emotional life is conditioned to form a good personality; 5) The acceleration and escalation programme of the early childhood gifted learning system is carried out based on Developpentally Appropriate Practice (DAP). and 6) The Teacher Professional Education (PPG) study program as a forum for assessment and research for the implementation of inclusive education for gifted children effectively.